KARAKTERISTIK BIJI DAN PERTUMBUHAN SEMAI SENGON DARI POLONG POHON INDUK SEHAT DAN TERSERANG KARAT TUMOR - , LATIF HANAFIANTORO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background of this research that many falcatariaâs seed derived from the free market and cultivated farmers is unknown origin and status of origin clearly, so the seed characteristics is need for detection. The objectives are (1) to compare falcatariaâs seed morphological characters, (2) evaluate the quality of the seedâs germination test, cutting test and tetrazolium test, (3) evaluate the ability of seedling growth. The materials used are seeds of the falcatariaâs tree healthy and gall rustinfected trees caused by the fungus Uromycladium tepperianum and performed by 4 replicate . Quantitative data analysis was conducted using the mean and T-test using SAS 9.1 program. Qualitative data were analyzed with descriptive analysis. The results showed that falcatariaâs seed morphological characteristics of healthy and rust-infected tumors is no significant difference. Evaluation of falcatariaâs seed viability by using cutting-test and tetrazolium method showed that seed comes from healthy trees have better grain quality than from trees infected with gall-rust fungus. Evaluation of seedling growth in general is falcatariaâs seeding was infected rust fungus tumors, on the leaves and shoots.